Hierarchical HZSM-5 for catalytic cracking of oleic acid to biofuels - Mahashanon Arumugam; Goh, Chee Keong; Zulkarnain Zainal; Sugeng Triwahyono; Adam F. Lee; Karen Wilson; Yap, Taufiq Yun Hin (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Solid acid catalyzed cracking of waste oil-derived fatty acids is an attractive route to hydrocarbon fuels. HZSM-5 is an effective acid catalyst for fatty acid cracking; however, its microporous nature is susceptible to rapid deactivation by coking. We report the synthesis and application of hierarchical HZSM-5 (h-HZSM-5) in which silanization of pre-crystallized zeolite seeds is employed to introduce mesoporosity during the aggregation of growing crystallites. The resulting h-HZSM-5 comprises a disordered array of fused 10–20 nm crystallites and mesopores with a mean diameter of 13 nm, which maintain the high surface area and acidity of a conventional HZSM-5. Mesopores increase the yield of diesel range hydrocarbons obtained from oleic acid deoxygenation from ~20% to 65%, attributed to improved acid site accessibility within the hierarchical network.